On the Regulatory Regime of Private Individuals - V. F. Popondopulo (Теоретическая и прикладная юриспруденция)
The article assesses the quality of legislation regulating the participation of individuals, both from a formal legal point of view (form) and in terms of its social purpose (content). One of the criteria for assessing the quality of legislation is the regulatory regime of the subjects. The difference between the regulatory regime of private individuals and the regulatory regime of public authorities is shown. A list of tasks that can be understood and resolved to a large extent in the legal nature of legislation is provided. One such task is considered — the task of determining the purpose and subject of legislative regulation. The Russian Civil Code is assessed as a system-forming piece of legislation of all Russian legislation. On the basis of the assessment of the state of Russian legislation, it is concluded that the federal law on regulations, which will regulate all the main aspects of legislative and other normative activities: the concept of legislation; Regulatory boundaries Principles of regulatory activity (based on the objectives and subjects of regulation, taking into account the differences in the nature of human activities and the activities of political institutions); types of regulations and their relationship with each other (legislative and by-laws; federal, regional and local acts; centralized and local acts; general and special acts, etc.), including case law, customs, universally accepted principles and norms of international law, international treaties; other aspects corresponding to the content of such a law (in particular, the drafting of the bill, including its public discussion, adoption, publication, modification and repeal, etc.). The determining principle in all cases should be the recognition, observance and protection by the state of the rights and freedoms of a person and a citizen as the highest value (Article 2 of the Russian Constitution).